ANALYSIS OF THE PHYSICOCHEMICAL PARAMETERS IN RAW MATERIAL MILK DETERMINED ACCORDING TO THE MILKING SYSTEMS USED - Victoria Codău (Furcea); Marian Mihaiu; Vlad Luca; Daiana-Alexandra Platon; Maria Crăciun (Agricultura)
This study determined the physicochemical properties of raw milk according to the milking system used. The raw material milk was collected from 10 holdings with different forms of ownership, with different technical equipment and different milking systems. Raw material milk parameters were analyzed: fat, protein, lactose, non-fat dry substance by the rapid method with the Bentley 150 analyzer.The milk from the mechanized systems is of high physicochemical quality, recording values of the quality parameters without much variation almost throughout the year, regardless of the dominant breed and the milking equipment used.